Left main bronchus separation after blunt trauma - Lisowska, Hanna; Marciniak, Marek; Pawełczyk, Konrad (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Tracheobronchial damage is very rare in clinical practice and represents no more than 1% of all injuries caused by blunt trauma. Nearly 80% of patients die before reaching the hospital. Most ruptures are observed in the right main bronchus and are located within 2 cm of the carina trachea. The highest mortality rate applies to patients with bilateral bronchial injuries. Nonspecific symptoms, additionally masked by complaints regarding other damaged organs, delay the diagnosis and surgical treatment. The aim of this article is to present one particular clinical case and to discuss it in conjunction with a literature review.